Healthy food for Dylan - Sarah, Duchess of York, 1959-; Cunliffe, Ian (New York : Sterling Children's Books, 2011)
Dylan does not like to eat many kinds of food until Cousin Abby shows him how to make Mr. Cheesy for lunch. Includes ten hints for parents to help children eat healthy foods.
School Library Journal
School Library Journal, August 2011
2.3
K-3.
K-3
Keywords: Food habits -- Juvenile fiction; Nutrition -- Juvenile fiction; Food habits -- Fiction; Nutrition -- Fiction; Eating customs -- Fiction; Nutrition -- Fiction; Picture books for children